2019
DOI: 10.1038/s41598-018-38374-w
|View full text |Cite
|
Sign up to set email alerts
|

Human trophoblast requires galectin-3 for cell migration and invasion

Abstract: Invasive extravillous cytotrophoblast of the human placenta expresses galectins-1, -3, and -8 in vivo and in vitro. This study aimed to investigate the potential role of galectin-3 in cell migration and invasion, using recombinant human galectin-3 (rhgalectin-3), small molecule galectin inhibitor I47, and galectin-3 silencing. HTR-8/SVneo cell migration was stimulated by rhgalectin-3 and reduced by I47, which could be neutralised by rhgalectin-3. Inhibitor specificity and selectivity for the galectins expresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 73 publications
(100 reference statements)
3
29
0
2
Order By: Relevance
“…In addition, our analysis of EVT gal‐3 expression revealed that the chimera lectin is highly expressed in the EVT layer of the human placenta. This observation is in agreement with previous studies showing that both interstitial and endovascular EVT are main sources of gal‐3 10 and with the recently established role of gal‐3 as a component of the human trophoblast invasion machinery 26 . The functional studies reported here have confirmed that gal‐3 participates in trophoblast cell migration/invasion.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, our analysis of EVT gal‐3 expression revealed that the chimera lectin is highly expressed in the EVT layer of the human placenta. This observation is in agreement with previous studies showing that both interstitial and endovascular EVT are main sources of gal‐3 10 and with the recently established role of gal‐3 as a component of the human trophoblast invasion machinery 26 . The functional studies reported here have confirmed that gal‐3 participates in trophoblast cell migration/invasion.…”
Section: Discussionsupporting
confidence: 93%
“…implantation 19,20 . Subsequent studies have revealed that endometrial gal-3 is involved in embryo implantation 21 and dysregulation of placental gal-3 is associated with adverse pregnancy outcomes [12][13][14][15][16]22,23 . The present study demonstrates that gal-3 is critical for orchestrating healthy fetal-maternal interface interactions and its dysregulation results in asymmetric FGR.…”
Section: Discussionmentioning
confidence: 99%
“…Galectin-3 was initially reported to be a factor related to endometrial receptivity due to its increased expression in the endometrium and trophoblast during embryo implantation 19 , 20 . Subsequent studies have revealed that endometrial gal-3 is involved in embryo implantation 21 and dysregulation of placental gal-3 is associated with adverse pregnancy outcomes 12 16 , 22 , 23 . The present study demonstrates that gal-3 is critical for orchestrating healthy fetal-maternal interface interactions and its dysregulation results in asymmetric FGR.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, LGALS3 gene (encoding galectin-3) was downregulated in trophoblasts from CZS-affected twins after ZIKV BR infection. LGALS3 is a galectin that has been described as involved in the process of trophoblast cell migration and invasion, significant for human embryo implantation [ 92 , 93 ]. Overall, downregulation of genes involved in trophoblast adaptation to the intrauterine environment, including ITGA1 , COL3A1 and LGALS3 ( S9 Fig ), in the trophoblasts of CZS-affected twins after ZIKV BR infection, may affect trophoblast migration, implantation, homeostasis and possibly impair the control of ZIKV BR infection.…”
Section: Discussionmentioning
confidence: 99%